2015
DOI: 10.1155/2015/304149
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium NCIMB 10415 Modulates Epithelial Integrity, Heat Shock Protein, and Proinflammatory Cytokine Response in Intestinal Cells

Abstract: Probiotics have shown positive effects on gastrointestinal diseases; they have barrier-modulating effects and change the inflammatory response towards pathogens in studies in vitro. The aim of this investigation has been to examine the response of intestinal epithelial cells to Enterococcus faecium NCIMB 10415 (E. faecium), a probiotic positively affecting diarrhea incidence in piglets, and two pathogenic Escherichia coli (E. coli) strains, with specific focus on the probiotic modulation of the response to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 70 publications
4
34
0
Order By: Relevance
“…The increasing application of probiotics in animal disease prevention and treatment requires an investigation of the underlying mechanisms of their health‐promoting effects (Klingspor et al . ). The findings of our study provide insights into the mechanism by which the HDRsEf1 strain protects cells against infection.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The increasing application of probiotics in animal disease prevention and treatment requires an investigation of the underlying mechanisms of their health‐promoting effects (Klingspor et al . ). The findings of our study provide insights into the mechanism by which the HDRsEf1 strain protects cells against infection.…”
Section: Resultsmentioning
confidence: 97%
“…Probiotics have been speculated to function via several proposed mechanisms including suppression of the growth and inhibition of pathogenic bacteria, improving the barrier function of the intestinal epithelium, and altering the immune activity of the host (Klingspor et al . ). Enterotoxigenic Escherichia coli (ETEC) is a major cause of traveller's diarrhoea and infectious diarrhoea in children in developing countries, and porcine ETEC has been reported to be the leading cause of postweaning diarrhoea (PWD) in pigs (Croxen and Finlay ).…”
Section: Introductionmentioning
confidence: 97%
“…Diarrhea: 2.95E-04 vs. 3.19E-05 and 1.54E-04 vs. 4.74E-05 for the relative abundance of E. faecalis and E. faecium , respectively). It has been suggested that E. faecium is capable of modulating barrier function of the porcine intestinal mucus (Bednorz et al, 2013; Klingspor et al, 2015). In weaned piglets, the dietary addition of E. faecalis LAB31 may increase the abundance of Lactobacillus and consequently reduce diarrhea (Hu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They have been described in a range of species (40,44,46), including vertebrates (41) and among those, humans (47). Lack of the 70-kilodalton family of HSPs (HSP70), a highly conserved protein promoter of heat tolerance (46), induces heat shock sensitivity in E. coli strains that would be otherwise resistant to that type of stress.…”
Section: Molecular Consequences During Fever: a Theorymentioning
confidence: 99%